Portmahomack Monastery of the Picts - Carver, Martin (Edinburgh University Press, 2022)
An archaeological window on a thousand formative years of the making of ScotlandPortmahomack today is a serene fishing village on the Dornoch Firth, north east Scotland where archaeological excavations have written a new history of the origins of Scotland. This book brings alive the expedition and its discoveries, most famously a monastery of the eighth century in the land of the Picts.Starting from chance finds of a Pictish carved stone in St Colman's churchyard, the archaeologists unearthed four settlements one on top of the other. An elite farm was succeeded by the Pictish monastery, which, following a Viking raid in AD800, became a trading place and then a medieval village. Scientific analysis shows at each stage where the people came from, their life-style and what they ate. Together it creates a story of the heroic adaptation of a European nation to new politics between the sixth and sixteenth century.The Picts were the outstanding sculptors of their day, producing carved stone monuments equal to anything being made in contemporary Europe. They were Britons, who resisted the Romans invaders and created their own warrior nation in the north east of the island. Coming under pressure from the Scots and the Norse, they disappeared from history in the ninth century AD. Now archaeology is finding them again.This massively updated new edition follows eight years intensive research on the huge assemblage of artefacts, human bone, animal bone and plant remains that were recovered. This has revealed a world of high mobility, rich in ideas and constantly changing it political orientation in a greater European context